Hacia la convergencia mundial del marco conceptual para la preparación de los estados financieros - Díaz Durand, Mario (2010)
Due to the current globalization in business and investments that generate a highly interrelated business world, it is a must to have a common standard in accounting that brings transparency and the real use of information. According to that, this article presents a comparative analysis of the conceptual framework for the preparation and presentation of financial statements of the two important international accounting models of normative use: the accounting standards established by the FASB and the IASB. The conceptual framework provides a guideline to prepare and present financial statements and at the same time it is a basis for the enactment of international financial reporting standards. To this day, there are some convergence agreements on conceptual frameworks between FASB and IASB, in charge of producing standards, which implies joint work in relation to their respective frameworks, with the purpose of developing a better conceptual framework, common for both institutions. With respect to this, in the article we can find proposals and reflections related to the convergence of conceptual frameworks, in order to enable the feasibility of a convergent framework as an important document in the revision and the issuance process of future international financial reporting standards.